Dynamic manoeuvres on MRI in oral cancers – A pictorial essay - Shah, Diva (Indian Journal of Radiology and Imaging, 2020)
Magnetic resonance imaging has been shown to be a useful tool in the evaluation of oral malignancies because of direct visualization of lesions due to high soft tissue contrast and multiplanar capability. However, small oral cavity tumours pose an imaging challenge due to apposed mucosal surfaces of oral cavity, metallic denture artefacts and submucosal fibrosis. The purpose of this pictorial essay is to show the benefits of pre and post contrast MRI sequences using various dynamic manoeuvres that serve as key sequences in the evaluation of various small oral (buccal mucosa and tongue as well as hard/soft palate) lesions for studying their extent as well as their true anatomic relationship.
Keywords: Dynamic manoeuvres; MRI; oral cavity lesions